A review on the use of audiovisual as media in improving listening skills among junior high school students - Syarifah Intan; Syamsul Bahri Yusuf; Diana Fauzia Sari (English Education Journal, 2022)
This research aims to analyze the effectiveness of audiovisual as media to improve junior high school students in listening skill. Based on data and information that are all taken from previous studies, it revealed that the students’ average score in listening were still low. Therefore, in order to help students to improve their listening skill, audiovisual media is a media which gave good effect on students’ listening skill. This research using library research as the method that concerned on how the use of audiovisual media can improve students’ listening skill based on the previous studies and the theories of the experts. Thus, the data was collected from previous studies related to audiovisual media and paraphrased to get information about audiovisual media, this data analysis technique includes the processes of data identification from relevant literature sources, determining where the data is located, obtaining the data, evaluating the data, and incorporating the data into the research presentation. Based on the result of this research, it showed that audiovisual media had positive effect on students’ listening skill. Moreover, several studies revealed that the students gave positive attitudes towards the use of audiovisual media. In addition, audiovisual media also encouraged and motivated students during the process of teaching and learning.